Endometrial cell‑derived exosomes facilitate the development of adenomyosis via the IL‑6/JAK2/STAT3 pathway - Jiang, Xinchan; Chen, Xiaobo (Experimental and therapeutic medicine, 2023)
Interleukin (IL)-6 upregulation is involved in the pathogenesis of adenomyosis, but the underlying mechanism remains to be elucidated. Exosomes mediate intercellular communication, therefore the present study investigated whether endometrial cell-derived exosomes mediated the crosstalk between the endometrium and the myometrium via IL-6 signaling. Primary adenomyotic myometrial (AM) cells and eutopic endometrial cells were isolated from patients with adenomyosis. Exosomes were obtained from endometrial cells and incubated with AM cells in the presence or absence of tocilizumab (an IL-6 inhibitor). MTT, flow cytometry and wound-healing assays were performed to examine AM cell proliferation, apoptosis, cell cycle distribution and migration. Western blotting and reverse transcription-quantitative PCR were conducted to determine the expression of the IL-6/Janus kinase 2 (JAK2)/STAT3 pathway proteins. Incubation with endometrial cell exosomes suppressed cell apoptosis of AM cells compared with controls, accompanied by increases in IL-6 production and JAK2/STAT3 phosphorylation. Endometrial cell exosomes promoted cell proliferation, increased the percentage of S-phase cells and enhanced the migration of AM cells. These effects were completely reversed by tocilizumab, along with substantial decreases in IL-6 production and JAK2/STAT3 phosphorylation. Endometrial cell-derived exosomes promote cell proliferation, migration and cell cycle transition of AM cells through IL-6/JAK2/STAT3 activation, facilitating the development of adenomyosis by mediating the crosstalk between the endometrium and the myometrium, and IL-6 targeted therapy could be a complementary approach against adenomyosis.